(untitled) (Journal of the Bangladesh Agricultural University, 2010)
The present study was performed in the Upazila Veterinary Hospital, Meghna, Comilla during the period from September 2006 to February 2007 to observe the prevalence of Foot and Mouth Disease (FMD) in cattle at Meghna upazila in Comilla. A total of 253 skin diseased cattle head were examined in this study where 109 were males and 144 were females. The prevalence of FMD was 24.51% at Meghna upazila. The effect of age, sex, breed, season and farming system on the incidence rate of the disease was discussed. Seasonal variation on outbreak of this disease was significantly higher. The clinical prevalence of FMD was highest in the month of November (34.69%) and December (36.20%). The males (35.77%) were more susceptible than females (15.97%). The adult cattle (34.18%) were more susceptible compared to heifer (23.43%) and young (09.72%). In breed, 39.18% indigenous breeds and 15.38% crossed breeds were infected by FMD. So, it could be concluded that the rural farming system, adult, male and the indigenous cattle were more susceptible to FMD in winter season. Keywords: Foot and Mouth Disease; Epidemiology; Clinical features; Breed DOI: 10.3329/jbau.v7i2.4741 J. Bangladesh Agril. Univ. 7(2): 317-319, 2009